Pilot Study in Qualitative Research: The Roles and Values - Roksana Janghorban; Robab Latifnejad Roudsari; Ali Taghipour (Tehran University of Medical Sciences, 2014)
A pilot or preliminary study is referred to a small-scale of a complete survey or a pretest for a particular research instrument such as a questionnaire or interview guide (1). Pilot studies could be conducted in qualitative, quantitative, and even mixed methods research (2).   General application of pilot studies can be summarized in four areas: 1) to find problems and barriers related to participantschr('39') recruitment 2) being engaged in research as a qualitative researcher 3) assessing the acceptability of observation or interview protocol and 4) to determine epistemology and methodology of research. Three specific functions of pilot studies in qualitative research are assigned to three main qualitative methodologies including phenomenology, grounded theory, and ethnography. It allows exercising epoch within the phenomenological research, increasing theoretical sensitivity in grounded theory, and familiarity with fieldwork in ethnography (3-5).